The 9th IEEE International Conference on Nano/Micro Engineered and Molecular Systems (NEMS) 2014
DOI: 10.1109/nems.2014.6908896
|View full text |Cite
|
Sign up to set email alerts
|

A novel micromixer with multimixing mechanisms for high mixing efficiency at low Reynolds number

Abstract: In this paper, we propose a novel passive micromixer structure for high mixing efficiency based on the combination of multimixing principles. With a special structure, our proposed micromixer can create vortices, transversal flows and chaotic advections to provide high mixing efficiency event at low Reynolds number. Moreover, two narrow slits at two ends of each mixing unit remarkably reduce pressure drop, making it easy to be built into micro-devices. We conduct intensive simulation to evaluate the performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Simulation results showed that it retained a high mixing efficiency of over 80% for a low Reynolds number of between 0.5 and 60 with a total mixing length of 3870 μm. Combining this micromixer with the unbalanced splits and cross-collisions of fluids, an improved micromixer with shifted trapezoidal chambers and a total mixing length of 5000 μm was then presented and shown in Figure 18 a [ 109 ]. Simulation results showed that the mixing efficiency was over 80% for an entire range of Reynolds numbers from 0.5 to 100.…”
Section: Passive Micromixermentioning
confidence: 99%
“…Simulation results showed that it retained a high mixing efficiency of over 80% for a low Reynolds number of between 0.5 and 60 with a total mixing length of 3870 μm. Combining this micromixer with the unbalanced splits and cross-collisions of fluids, an improved micromixer with shifted trapezoidal chambers and a total mixing length of 5000 μm was then presented and shown in Figure 18 a [ 109 ]. Simulation results showed that the mixing efficiency was over 80% for an entire range of Reynolds numbers from 0.5 to 100.…”
Section: Passive Micromixermentioning
confidence: 99%
“…Nguyen et al 21 found that the 3D Tesla structure works well at a Reynolds number ( Re ) > 5 for solution mixing. Re > 100 is uncommon in passive micromixers due to the limited pumping capacity to achieve a high Reynolds number 22–26. However, in this study, the upper limit of Re = 140 was chosen rather than 100 to observe anomalies.…”
Section: Methodsmentioning
confidence: 99%
“…Simulation results showed that it retained a high mixing efficiency of over 80% for a low Reynolds number of between 0.5 and 60 with a total mixing length of 3870 µm. Combining this micromixer with the unbalanced splits and cross-collisions of fluids, an improved micromixer with shifted trapezoidal chambers and a total mixing length of 5000 µm was then presented and shown in Figure 18a [109]. Simulation results showed that the mixing efficiency was over 80% for an entire range of Reynolds numbers from 0.5 to 100.…”
Section: Chamber Based Micromixersmentioning
confidence: 99%